Plaster of Paris (POP) Installers' Awareness of Occupational Hazards and Utilisation of Safety Measures in Ho Municipality, Ghana. Issue 1 (31st December 2023) - Novieto, Divine Tuinese; Apawu, Raymond Kirk; Apprey, Michael Wellington; Ahiabu, Moses K.
Abstract: Construction workers are found to use Personal Protective Equipment (PPE) infrequently, although workplace accidents are common and strongly associated with safety education. In Ho, Ghana, this study examines POP installers' awareness of occupational hazards and the use of PPEs. The study's motivation and contribution are in its analysis of the perceived obstacles and driving forces behind PPE use by POP installers in the construction industry, which is yet unknown in Ghana. Between May 15 and June 30, 2022, 149 POP installers in Ho Municipality filled out a crosssectional questionnaire using a purposive sampling method, and the data were analysed using the Statistical Package for Social Science (SPSS) v.20. The outcome variables were determined using logistic regression with a 0.05 p value, the relative importance index (RII), and correlation analysis. There is a lack of awareness of knowledge, PPE use, and workplace safety among the participants. Once again, respondents cited discomfort as a reason for not wearing PPE during POP installation. Furthermore, knowledge of occupational hazards among POP workers negatively predicts PPE usage (B = 0.207, p < 0.05). The study's findings provide critical information for contractors' associations to collaborate with relevant health and safety professionals to regularly organise safety awareness training for members to increase worker knowledge and reduce risk-taking behaviour. This study is unique because it is the first to access and provides an in-depth analysis of the purported barriers and driving motivations for PPE compliance and non-compliance from the perspective of an under-researched group of construction workers in Ghana.